Urban Tropospheric Ozone Increases the Prevalence of Vitamin D Deficiency among Belgian Postmenopausal Women with Outdoor Activities during Summer - Manicourt, Daniel-Henri; Devogelaer, Jean-Pierre (The journal of clinical endocrinology and metabolism, 2008)
Context: By absorbing sunlight UVB and thereby reducing cutaneous vitamin D photosynthesis, ozone, a common urban pollutant, could cause hypovitaminosis D. Objectives: The objective of the study was to establish the characteristics and percentage of subjects with serum 25-hydroxyvitamin D [25(OH)D] less than 75 nmol/liter among postmenopausal women engaging in outdoor activities in either Brussels or the countryside. Design/Setting: This was a cross-sectional study conducted in a university research hospital. Patients/Methods: Among 249 women consulting for either shoulder tendonitis or lumbar spine osteoarthritis, 121 free of conditions and drugs affecting bone and calcium metabolism completed two food-frequency questionnaires within 15 d and we selected the 85 subjects with retest scores within the ± 15% of test scores. Other parameters included sun exposure index (SEI), PTH levels, and femoral neck T-score. Results: Urban residents (n = 38) and rural residents (n = 47) did not differ in mean ages, body mass indices, and vitamin D intakes. When compared with rural inhabitants, urban inhabitants were exposed to ozone levels 3 times higher, and despite a higher mean SEI (113 vs. 87; P < 0.001), they had a higher prevalence of 25(OH)D less than 75 nmol/liter (84 vs. 38%). After adjusting for SEI, 25(OH)D was 2-fold higher in rural residents, and after adjusting for 25(OH)D, SEI was 3-fold higher in urban residents. Femoral neck T-scores correlated positively with 25(OH)D and negatively with PTH levels. Conclusions: Air pollution may be a neglected risk factor for hypovitaminosis D, which is known to compromise several health outcomes. As long as 25(OH)D is greater than 75 nmol/liter, calcium intakes greater than 17.5 mmol/d are unnecessary to prevent elevations in PTH levels.